The Relationship Between Knowledge, Attitudes and Actions with the Provision of Clean Water in Hamlet 16 Bagan Percut, Deli Serdang Regency - Meutia Nanda; Annisa Humaira; Sumiarti Purba; Dini Azila Saragih; Muhammad Rizky Ramadhan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
It is important to investigate how knowledge, attitudes, and behaviors are connected to the provision of clean water to understand the health behavior of environmental communities. These three elements are interrelated and interconnected. Good knowledge of clean water can form a positive attitude towards the importance of keeping water clean, which in turn can encourage individuals or groups to take actions that support the better provision of clean water for the community. In Hamlet 16 Bagan Percut Sei Tuan, the researcher aims to find out knowledge, attitudes, and behaviors through the provision of clean water. There were 300 participants in the study, and 51 samples were randomly selected for the study. This study uses a cross-sectional design and a descriptive model as the quantitative technique. With a P value of 0.001 < 0.05, there is a strong relationship between knowledge and the availability of clean water. With a P value of 0.167 < 0.05, there was no real correlation between knowledge and the availability of clean water. Action and availability of clean water were significantly correlated, with P values of 0.001 < 0.05. It is hoped that the community in Hamlet 16 Bagan Percut Sei Tuan will be more in providing clean water because the behavior, awareness, and active participation of the community directly affect the success and sustainability of clean water supply efforts.